2000
DOI: 10.1136/heart.84.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery compliance and adaptive vessel remodelling in patients with stable and unstable coronary artery disease

Abstract: Objective-To test the hypothesis that patients with unstable coronary syndromes show accentuated compensatory vessel enlargement compared with patients with stable angina, and that this may in part be related to increased coronary artery distensibility. Design and patients-In 23 patients with unstable coronary syndromes (10 with non-Q wave myocardial infarction and 13 with unstable angina), the culprit lesion was investigated by intravascular ultrasound before intervention. The vessel cross sectional area (VA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Recent intravascular ultrasound (IVUS) studies have indicated that culprit lesions in ACS are characterized by large eccentric plaques with an echolucent zone, ulceration, thrombus formation, spotty calcium deposits and more positive remodeling compared with culprit lesions in stable angina pectoris or non-culprit lesions in ACS [4][5][6][7][8][9][10][11][12][13], and that culprit coronary artery walls are more distensible in ACS than in stable angina [14,15]. Coronary artery distensibility has been studied using IVUS imaging and it is reportedly determined by age, diabetes mellitus, and the size or thickness, eccentricity, composition and remodeling of the imaged plaque [14][15][16][17][18][19][20][21][22]. However, how increased vessel distensibility in the ACS-related coronary artery contributes to unstable clinical manifestations has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent intravascular ultrasound (IVUS) studies have indicated that culprit lesions in ACS are characterized by large eccentric plaques with an echolucent zone, ulceration, thrombus formation, spotty calcium deposits and more positive remodeling compared with culprit lesions in stable angina pectoris or non-culprit lesions in ACS [4][5][6][7][8][9][10][11][12][13], and that culprit coronary artery walls are more distensible in ACS than in stable angina [14,15]. Coronary artery distensibility has been studied using IVUS imaging and it is reportedly determined by age, diabetes mellitus, and the size or thickness, eccentricity, composition and remodeling of the imaged plaque [14][15][16][17][18][19][20][21][22]. However, how increased vessel distensibility in the ACS-related coronary artery contributes to unstable clinical manifestations has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]28,35,36 Furthermore, previous IVUS studies have consistently demonstrated that lesions with positive remodeling were associated with worse clinical outcomes. 15,19,36 -40 In our present study population, 12-month clinical follow-up did not show any prognostic impact of the arterial and fibrous cap remodeling because of the small sample size and short follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…18 On the other hand, negative (inadequate) arterial remodeling or vessel shrinkage is associated with lumen narrowing in a majority of patients with stable angina pectoris. [5][6][7]28,31 Although the exact mechanism for extent and direction of arterial remodeling is not fully understood, it is suggested that intraplaque cytokines such as matrix metalloproteinases may cause disruption of the media and induce subsequent positive arterial remodeling. 9,10 On the other hand, it also is reported that matrix metalloproteinases may cause thinning and ultimate disruption of the fibrous cap, resulting in plaque rupture and acute coronary syndrome or sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECM protein expression is associated with neoangiogenesis and unstable plaques [47]. Positive vascular remodeling of coronary atherosclerotic plaques has been found postmortem in the majority of patients with a myocardial infarction [48]. To detect and characterise these mechanisms, an elastin-specific Gd-labeled low-molecular-weight probe (855.95 Da) has been successfully used to target elastin expression in initial stages of coronary artery disease in a mouse and swine model of atherosclerosis (Fig.…”
Section: Targeting Extracellular Plaque Componentsmentioning
confidence: 99%